2015
DOI: 10.1103/physrevb.91.115117
|View full text |Cite
|
Sign up to set email alerts
|

Strongly correlated states of trapped ultracold fermions in deformed Landau levels

Abstract: We analyze the strongly correlated regime of a two-component trapped ultracold fermionic gas in a synthetic non-Abelian U (2) gauge potential, that consists of both a magnetic field and a homogeneous spin-orbit coupling. This gauge potential deforms the Landau levels (LLs) with respect to the Abelian case and exchanges their ordering as a function of the spin-orbit coupling. In view of experimental realizations, we show that a harmonic potential combined with a Zeeman term, gives rise to an angular momentum te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 112 publications
(169 reference statements)
0
4
0
Order By: Relevance
“…In previous works, theoretical investigations have shown that synthetic non-Abelian gauge potentials are an efficient way of implementing exotic quantum Hall systems [44][45][46][47][48][49][50] or topological phases [51][52][53][54][55] in two-dimensional lattices, and that laser assisted tunneling may provide useful tools for the simulation of particles like massless Dirac fermions [45], Wilson fermions [56] or Weyl fermions [57].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous works, theoretical investigations have shown that synthetic non-Abelian gauge potentials are an efficient way of implementing exotic quantum Hall systems [44][45][46][47][48][49][50] or topological phases [51][52][53][54][55] in two-dimensional lattices, and that laser assisted tunneling may provide useful tools for the simulation of particles like massless Dirac fermions [45], Wilson fermions [56] or Weyl fermions [57].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the tunability of the experimental parameters, another important advantage of considering ultracold atom systems is that in these setups one can also study generalizations of the Abelian π-flux model that involve artificial non-Abelian gauge potentials [36], including the effects of a spin-momentum coupling independent on the position. In previous works, theoretical investigations have shown that synthetic non-Abelian gauge potentials are an efficient way of implementing exotic quantum Hall systems [44][45][46][47][48][49][50] or topological phases [51][52][53][54][55] in two-dimensional lattices, and that laser assisted tunneling may provide useful tools for the simulation of particles like massless Dirac fermions [45], Wilson fermions [56] or Weyl fermions [57].…”
Section: Introductionmentioning
confidence: 99%
“…For example, one can create quasi-periodic onedimensional systems (Amico et al 2005), realise p-band condensates (Wirth et al 2011(Wirth et al , Ölschläger et al 2013, or even do atomtronics (Seaman et al 2007), which aims at simulating electronic circuits. Due to this great flexibility, the recent realisation of topological states in condensed-matter systems (König et al 2007, Hasan and Kane 2010, Qi and Zhang 2010 has sparked a flurry of activities in the field of cold atoms, aiming at reproducing, engineering, and manipulating these fascinating quantum states in traps (Roncaglia et al 2011, Corman et al 2014, Burrello et al 2015 and in optical lattices (Hemmerich and Morais Smith 2007, Aidelsburger et al 2013, Miyake et al 2013, Jotzu et al 2014, Aidelsburger et al 2015, Chomaz et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…The recent realisation of topoplogical states in condensed-matter systems (König et al 2007, Hasan & Kane 2010, Qi & Zhang 2010 has sparked a flurry of activities in the field of cold atoms, aiming at reproducing, engineering, and manipulating these fascinating quantum states in traps (Roncaglia et al 2011, Corman et al 2014, Burrello et al 2015 and in optical lattices (Hemmerich & Morais Smith 2007, Aidelsburger et al 2013, Miyake et al 2013, Jotzu et al 2014, Aidelsburger et al 2015, Chomaz et al 2015.…”
Section: Introductionmentioning
confidence: 99%